2020
DOI: 10.1371/journal.pone.0242620
|View full text |Cite
|
Sign up to set email alerts
|

Morphological description of a novel synthetic allotetraploid(A1A1G3G3) of Gossypium herbaceum L.and G.nelsonii Fryx. suitable for disease-resistant breeding applications

Abstract: Wild species of Gossypium ssp. are an important source of traits for improving commercial cotton cultivars. Previous reports show that Gossypium herbaceum L. and Gossypium nelsonii Fryx. have better disease resistance characteristics than commercial cotton varieties. However, chromosome ploidy and biological isolation make it difficult to hybridize diploid species with the tetraploid Gossypium hirsutum L. We developed a new allotetraploid cotton genotype (A1A1G3G3) using a process of distant hybridization with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Research on cotton resistance started late, however has progressed rapidly in recent years. At home and abroad, the collection, assessment and verification of cotton resistant germplasm resources on the non-biotic resistance of cotton ( Nazeer et al, 2014 ; Yin et al, 2020 ) such as salt resistance, drought resistance, polar temperature tolerance, and soil trophic stress, and a number of important resistant germplasm resources were discovered. It is an important raw material for the resistance and breeding of cotton.…”
Section: Research Progress On Cotton Stress Resistance Breedingmentioning
confidence: 99%
“…Research on cotton resistance started late, however has progressed rapidly in recent years. At home and abroad, the collection, assessment and verification of cotton resistant germplasm resources on the non-biotic resistance of cotton ( Nazeer et al, 2014 ; Yin et al, 2020 ) such as salt resistance, drought resistance, polar temperature tolerance, and soil trophic stress, and a number of important resistant germplasm resources were discovered. It is an important raw material for the resistance and breeding of cotton.…”
Section: Research Progress On Cotton Stress Resistance Breedingmentioning
confidence: 99%
“…The growing number of evidences has been reported to verifying the adoptive roles of alien introgression for different quality traits, especially fiber quality ofG. hirsutum [62][63][64][65][66][67][68].…”
Section: Cotton Improvementmentioning
confidence: 99%
“…In the past few decades, the following studies were conducted on obtaining interspecific hybrids exploiting the genetic diversity of Gossypium germplasm: G. hirsutum × G. klotzschianum [ 32 ], G. hirsutum × G. trilobum [ 33 ], G. arboreum × G. anomalum [ 34 ], G. hirsutum × G. anomalum [ 35 ], G. herbaceum × G. australe [ 36 ], G. hirsutum × G. australe [ 37 ], G. hirsutum × G. arboreum [ 38 ], G. capitis-viridis × ( G. hirsutum × G. australe ) 2 [ 39 ], G. hirsutum × G. darwinii [ 40 ], G. herbaceum × G. nelsonii [ 41 ]. Despite an extensive literature review, no reports were found on obtaining allotetraploids using the cotton species G. herbaceum and G. mustelinum .…”
Section: Introductionmentioning
confidence: 99%